Advancing environmental sustainability concepts in medical radiation science education: A document analysis - Ago. J.L; Acquah. G; Ohene-Botwe. B; et al (Radiography, 2025)
Introduction: Medical radiation science (MRS) practices contribute significantly to the carbon footprint of healthcare. As the need for environmental sustainability (ES) increases, it is crucial to integrate ES concepts into MRS education curricula to prepare students for environmentally sustainable professional practice. Consequently, this document analysis examined current ES practices in MRS education and identified barriers and improvement strategies. Methods: A qualitative document analysis was conducted following the ‘READ’ (Readying, Extracting, Analysing, Distilling) approach. Data were retrieved from two databases (Scopus and PubMed) and MRS- specific journals and professional websites. Studies and documents published between 2015 to February 2025 that addressed ES practices, barriers, and improvement strategies in MRS education were included. Data were analysed using qualitative content analysis. Results: A total of 2330 articles and documents were identified, 11 of which met the selection criteria. Three themes emerged: (i) current ES practices in MRS education, (ii) barriers to improving ES practices in MRS education, and (iii) strategies for enhancing ES training. ES practices in MRS education include patient safety education through risk-benefit analysis and fostering research and collaboration, while insufficient knowledge and awareness and limited capacity (funding, resources, and time) were barriers identified. Strategies for improvement included raising ES awareness and adopting environmentally sustainable teaching practices. Conclusion: MRS education and training incorporate ES practices in line with the global call for sus tainable health professions education. Nonetheless, awareness creation and adoption of ES-oriented pedagogies could enhance MRS students’ confidence and attitudes towards planetary health. Implication for practice: To advance ES practices in MRS curricula, educators should practically incor porate them into teaching, learning, and assessment activities. This could be achieved through problem- based learning, case studies, interdisciplinary learning, and including ES concepts in rubrics. © 2025 The Author(s). Published by Elsevier Ltd on behalf of The College of Radiographers. This is an open access article under the CC BY license (http://creativecommons.org/licenses/by/4.0/).
Research Article
Keywords: Environmental sustainability; Planetary health; Medical radiation science